Differences of Main Levels of Serum P-Selectin and Trombosite in Severe Preeclampsia and Eclampsia - Serudji, Joserizal; Kartika, Yudha Meiriza; Erkadius, Erkadius (Andalas Obstetrics And Gynecology Journal, 2017)
Preeclampsia-eclampsia is a main complication of pregnancy in which the incidence is increasing world-wide and is associated with maternal morbidity and mortality. P-selectin (CD62P) is released from the cell surface and circulation as soluble molecules in the plasma. Both forms of, as membrane and soluble forms, p-selectin is an agonist of the process of thrombosis and inflammation. This research was conducted by cross sectional method in maternity emergency room of obstetrics and gynecology department of Central General Hospital of Dr. M. Djamil Padang from June 2015 through the sample size is met with 20 patients of severe preeclampsia and 8 patients of eclampsia, who met the inclusion criteria and there is no exclusion criteria. Then performed statistical analysis using t-test to determine differences in mean serum levels of p-selectin and platelet of severe preeclampsia and eclampsia. Differences in mean serum levels of p-selectin and plate-let in the two groups were statistically significant (p = 0.000). Activated platelets at eclampsia is higher than severe preeclampsia, which is indicated by the high levels of p-selectin serum and low platelets remaining in eclampsia than severe preeclampsia.Keywords: P-selectin, Platelet, Severe Preeclampsia, Eclampsia